Designing learning elements using the multiliteracies approach in an ESL writing classroom - Sarjit Kaur,; Malini Ganapathy,; Gurnam Kaur Sidhu, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2012)
Teaching English language literacy skills in contemporary ESL classrooms is evolving dynamically in cohesion with the multiplicity of communication channels, media, cultural and linguistic diversity (Kalantzis & Cope, 2009). Students engage with different texts according to their social and private contexts which include web-based stories, interactive stories, hyper narratives in computer games, internet, podcasting, online news, e-mail, text messaging, MSN, Facebook, Twitter, Skype and weblogs. These new practices fundamentally change students’ learning processes in the ESL classroom as they interact with various multimedia and deal with the multiplicity of communication channels and social networking. In addressing these new challenges, ESL students require new approaches to understand literacies used in making meanings from multimodal communication elements which is relevant when integrated into teachers’ pedagogical practices. This paper situates the framework of the Multiliteracies approach in reframing ESL teachers’ pedagogical repertoires with the aim of enhancing students’ writing performance. Using classroom observations and interviews, this qualitative case study examines the effectiveness of ESL teaching of writing using the Multiliteracies approach among 37 Chinese students in a secondary school in Penang, Malaysia. The results confirm the need for teachers to negotiate literacies through broad repertoires of multimodal pedagogical practices in the secondary school context as these elements promote positive learning outcomes. The implications of this study suggest that the Multiliteracies approach to writing lessons planned in accordance to the learning element results in pedagogical practices which are multimodal in nature and these appeal to students’ interest and motivate them to improve their writing performance